Pengaruh Perilaku Pemimpin, Karakteristik Pribadi, Lingkungan Kerja dan Pengharapan terhadap Kepuasan Kerja Karyawan PT Pupuk Sriwidjaja Palembang Sumatera Selatan - Widodo, H. Slamet (Universitas Brawijaya, Indonesia, 2008)
The aim of this research was to identify the effect of leader's attitudes, personal characteristics, work situation, and the expeciation to employees' working satisfaction. This study was executed at PT Pupuk Sriwijaya Palembang South Sumatera on the staff of Human Resource Division and General Compartmen through questionnaire with validated and reliable questions. The results indicated that (1) there was a direct effect of principal attitude on employee's working expectation, (2) the're relationship between personal characteristics with working expectation, (3) the're connection of working situation with working expectation, and (4) the're direct relationship between employees' working expectation with their working satisfaction. In view of these results, it is necessary for PT Pupuk Sriwijaya to improve employee working satisfaction by improving employer's attitude, enhancing their personal characteristics with which good situation in working place will increase.